The presentation of spontaneous coronary artery dissection in the emergency department: Signs and symptoms in an unsuspecting population. (26th December 2021) - Johnson, Alexis K.; Tweet, Marysia S.; Rouleau, Samuel G.; Sadosty, Annie T.; Hayes, Sharonne N.; Raukar, Neha P.
Abstract: Objectives: Spontaneous coronary artery dissection (SCAD) has emerged as a common cause of acute coronary syndrome (ACS) in young women, although it is rarely discussed in the differential diagnosis for chest pain in the emergency department (ED). In a population otherwise considered low risk for myocardial infarction, there is a danger of incomplete workup and missed diagnosis. In this study, we aim to describe the clinical presentation of those who present to the ED with SCAD to increase awareness of this potentially fatal diagnosis among emergency practitioners. Methods: Data were queried from the Mayo Clinic "Virtual" Multicenter SCAD Registry, a large multisite international disease registry. The registry includes demographic information as well as data from both medical records and surveys administered following the SCAD event. Symptom presentation was abstracted from survey narrative responses. Data analysis was performed using descriptive statistics. Results: Of 1196 subjects included, chest pain was reported during initial SCAD event in 95.7%. Most common chest symptoms descriptors were pain, pressure/weight, and tightness, with radiation most often in one or both arms/shoulders. Other common symptoms included nausea, shortness of breath, and diaphoresis. Most common electrocardiogram (ECG) findings reported were ST elevation, T‐wave abnormality, and normal ECG. Initial troponin values were within normal range in 20.1% of patients. Conclusion: With young healthy women often considered "low risk" for ACS, it is important to understand that SCAD is a cause of ACS, and familiarity with presentation can improve awareness among emergency physicians. Our data can provide insight in helping to identify young women who present with chest pain due to SCAD so they can be appropriately evaluated.